The Impact of the Unifying Curricula, Examination and Assessment System on the Academic Performance of the Second Intermediate Accounting Students in the Accounting Dept., at The University of Benghazi. - زاقوب, د. علي عوض; بالخير, أ.صالح أبوبكر (Dirasat in Economics and Business, 2021)
This study aimed to examine and evaluate the effect of the system of unifying curricula and examinations for the courses of accounting principles (1), principles of accounting (2), and intermediate accounting (1) on academic performance as measured by the results of students enrolled in intermediate accounting (2) in the Faculty of Economics at the University of Benghazi in Libya. The data were collected through the results of students enrolled in the intermediate accounting course (231) in the basic accounting courses in the spring semester of 2019. after analyzing the data using appropriate statistical methods, the study concluded that there is a positive effect of significant significance for the system of unifying curricula and examinations in basic accounting courses (accounting principles (1), accounting principles (2), and intermediate accou- nting (1)) on academic performance measured by the results of students enrolled in intermediate accounting (2) in the Faculty of Economics at the University of Benghazi. Therefore, this study recommended the need to continue applying this system in the accounting department and other departments of the Faculty of Economics and other colleges. This result provides insight into the importance of applying the system of unifying curricula and examinations and evaluation to enhance students' performance in accounting basic and advanced courses, which leads to an improvement in the general academic performance of the department's graduates. The results of this study also provide academic researchers with a useful basis for future studies related to the subject of this study, as these results are expected to serve as a basis forfuture studies in this field of research by re-examining the impact of various factors on studentts' performance in accountting courses at the overall academic level